The effects of retrenchment on organisational performance in Zimbabwe case study: National Foods Bulawayo 2008-2015 - Sengwe, Regina (Midlands State University, 2017)
The study was premised on exploring the effects of retrenchment on organizational performance in Zimbabwe with the utilization of National Foods Bulawayo as a case study. Herzberg’s Two Factor theory and Alicia et al’s Downsizing model anchored the study serving as its theoretical framework. Investigative research techniques were adopted by the researcher in unearthing the issues encompassed in the relationship between retrenchment and organizational performance. With the use of qualitative techniques. Using simple random sampling, 37 questionnaires were distributed to the general employees and 30 interviews were conducted with the middle and top management who were selected using purposive sampling in generating qualitative data. Thematic and content analysis were used to carry out data analysis. The research findings established that quality planning and employee dedication and trust are crucial elements in redeeming organizational performance through retrenchments. Measures such as market share, productivity and financial status were used to measure performance of National Foods Bulawayo. The findings established that NFB initiated retrenchment prematurely and its organizational performance did not improve as expected. The study concluded that there is need for the management to understand the implications of retrenchment, properly plan, whilst taking into considerations employee needs and feelings for the betterment of organizational performance through retrenchment. It was noted that the interference of the political climate in the activities of the organization disturbed the improvement of organizational performance, this calls for the need of the company to establish a strong corporate governance framework to improve efficiency at the organization. There is need for another research to be conducted at a different entity so as to determine if retrenchment is not truly efficient in improving organizational performance.